[Journal of Reverend Thomas Hamilton Fleming] - Fleming, Thomas Hamilton (Adam Matthew Digital, 1857)
Journal entries, Aug. 24, 1857-Aug. 7, 1859, describing missionary life and work amongst Native Americans and Inuit in Rupert's Land and Northwest Territories, including census statistics of June 1, 1858